Molecular detection of Clostridium difficile on inert surfaces from a Costa Rican hospital during and after an outbreak - Morales, Luisa (2016)
Background: Hospital transmission of Clostridium difficile is fostered by contamination of surfaces and medical equipment with spores highly resistant to disinfectants and regular cleaning procedures. Despite the outbreaks and fatalities that C difficile causes, its epidemiology has not been studied in hospitals from middle- and low-income countries. To tackle this knowledge gap, the detection frequency of C difficile DNA on inert surfaces of a major Costa Rican hospital during and after an outbreak was compared. Methods: We used a presence-absence real-time polymerase chain reaction to detect a fragment of the tpi gene of C difficile on 21 surface samples collected during an outbreak and 54 surface samples taken 2 years later at the same hospital. Results: C difficile DNA was detected in 40% of the 75 environmental samples analyzed. Whereas 71% of the samples collected during the outbreak were positive, only 28% of the samples obtained 2 years after the outbreak gave the same result. This 2.5× ratio was maintained when the comparison was restricted to the wards that were sampled both during and after the outbreak (72% vs 35%, P = .016). Conclusions: Our results show that environmental surfaces in the hospital analyzed are continuously being contaminated with C difficile DNA and that their level of contamination is higher during an outbreak than after it